2010
DOI: 10.1051/0004-6361/200913869
|View full text |Cite
|
Sign up to set email alerts
|

A new weapon for the interstellar complex organic molecule hunt: the minimum energy principle

Abstract: Context. The hunt for the interstellar complex organic molecules (COMs) supposed to be the building blocks of the molecules at the origin of life is a challenging but very expensive task. It starts with laboratory experiments, associated with theoretical calculations, that give the line frequencies and strengths of the relevant molecules to be identified and finishes with observations at the telescopes. Aims. The present study aims to suggest possible guidelines to optimize this hunt. Levering on the minimum e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 33 publications
6
62
1
Order By: Relevance
“…A further test would be to measure the abundance of the next C 2 H 5 NO isomer, acetimidic acid, CH 3 C(OH)NH which has a slightly higher zero-point energy than N-methylformamide (Lattelais et al 2010). This would require laboratory measurements to characterize the rotational spectrum of this molecule and produce spectroscopic predictions suitable for an astronomical search.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further test would be to measure the abundance of the next C 2 H 5 NO isomer, acetimidic acid, CH 3 C(OH)NH which has a slightly higher zero-point energy than N-methylformamide (Lattelais et al 2010). This would require laboratory measurements to characterize the rotational spectrum of this molecule and produce spectroscopic predictions suitable for an astronomical search.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest as a candidate for interstellar detection because its structural isomer acetamide (CH 3 CONH 2 ) has already been detected in the ISM (Hollis et al 2006;Halfen et al 2011). CH 3 NHCHO is the second most stable C 2 H 5 NO isomer after acetamide (Lattelais et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The cyclic isomers and those containing an NO bond were not considered for energetic reasons (Chiaramello et al 2005;Lattelais et al 2010).…”
Section: Neutral Glycine and Isomersmentioning
confidence: 99%
“…It is an important molecule for interstellar pre-biotic chemistry because it contains a peptide bond -C(=O)NH-that holds together the chains of amino acids. Recently it has been shown that of all possible simplest interstellar molecules that contain a peptide bond, formamide is the most stable energetically (Lattelais et al 2010). Formamide is a light molecule whose maximum absorption (emission) lies at about 650 GHz below 300 K and an intense spectrum that extends far beyond 1 THz.…”
Section: Introductionmentioning
confidence: 99%